European guidelines on perioperative venous thromboembolism prophylaxis: Aspirin. Issue 2 (February 2018) - Jenny, Jean-Yves; Pabinger, Ingrid; Samama, Charles Marc
Abstract : N/A: There is a good rationale for the use of aspirin in venous thromboembolism prophylaxis in some orthopaedic procedures, as already proposed by the 9th American College of Chest Physicians' guidelines (Grade 1C). We recommend using aspirin, considering that it may be less effective than or as effective as low molecular weight heparin for prevention of deep vein thrombosis and pulmonary embolism after total hip arthroplasty, total knee arthroplasty and hip fracture surgery (Grade 1C). Aspirin may be less effective than or as effective as low molecular weight heparins for prevention of deep vein thrombosis and pulmonary embolism after other orthopaedic procedures (Grade 2C). Aspirin may be associated with a low rate of bleeding after total hip arthroplasty, total knee arthroplasty and hip fracture surgery (Grade 1B). Aspirin may be associated with less bleeding after total hip arthroplasty, total knee arthroplasty and hip fracture surgery than other pharmacological agents (Grade 1B). No data are available for other orthopaedic procedures. We do not recommend aspirin as thromboprophylaxis in general surgery (Grade 1C). However, this type of prophylaxis could be interesting especially in low-income countries (Grade 2C) and adequate large-scale trials with proper study designs should be carried out (Grade 1C).